Respuesta :
18 = 2x -6 (Subtract 18 on both sides then subtract 2)
-2x = -6 -18
-6 -18 is = -24 (you add negative numbers together)
-2x = -24 (divide both numbers by -2)
X = 12
-2x = -6 -18
-6 -18 is = -24 (you add negative numbers together)
-2x = -24 (divide both numbers by -2)
X = 12
Answer:
18
X = ---- , y = 12
c
Step-by-step explanation:
Solve for x, y
X = 18
__
c
Y = 12, c ≠ 0
Consider the first equation. Subtract 2y from both sides.
cx - 2y = -6
To solve a pair of equations using substitution, first solve one of the equations for one of the variables. Then substitute the result for that variable in the other equation.
cx = 18, cx - 2y = -6
Pick one of the two equations which is more simple to solve for x by isolating x on the left hand side of the equal sign.
cx = 18
Divide both sides by c.
18
X = __
c
Substitute 18/c for x in the other equation,
c x - 2y = - 6.
18
c x ( ---- ) - 2y = - 6
c
18
Multiply c times ----
c
18 - 2y = - 24
Subtract 18 from both sides of the equation.
- 2y = - 24
Divide both sides by -2.
y = 12
The system is now solved.
18
X = ---- , y = 12
C